2018
DOI: 10.31234/osf.io/xk54t
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adults are more efficient in creating and transmitting novel signalling systems than children

Abstract: children Acknowledgement:We gratefully acknowledge funding of a research visit to the Language and Cognition Group of the Max-Planck-Institute of Psycholinguistics in Nijmegen, which supported the writing of this paper, and helpful discussions with Limor Raviv, Mark Dingemanse, Monica Tamariz, Seán Roberts and Stephen Levinson. We also wish to express our gratitude to Arduthie Primary School and Mill O'Forest Primary School, Stonehaven, for their support in running the experiments.Language transmission in adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 66 publications
1
23
0
Order By: Relevance
“…This level of structure is referred to as combinatorial structure and is assumed to arise from cognitive biases that favor reuse and modification of learned building blocks (Roberts & Galantucci, 2012, Verhoef et al, 2014. Iterated language learning experiments have explored a variety of signaling spaces such as sequences of letters (Kirby et al, 2008;, Carr et al, 2017Cornish et al, 2017), syllables , colors (Cornish et al, 2013), tones (Kempe et al, 2019) as well as drawn squiggles , tracings on a continuously moving pad (Galantucci, Kroos & Rhodes;, abstract graphical forms called Ferros (Cuskley, 2019), whistled pitch contours (Verhoef et al, 2014;, and manual gestures (Motamedi et al, 2019). These experiments have shown that both inter-generational transmission (Verhoef et al 2014) and referential communication (Little et al, 2017), can lead to the emergence of combinatorial structure.…”
Section: Combinatorial and Compositional Structurementioning
confidence: 99%
See 2 more Smart Citations
“…This level of structure is referred to as combinatorial structure and is assumed to arise from cognitive biases that favor reuse and modification of learned building blocks (Roberts & Galantucci, 2012, Verhoef et al, 2014. Iterated language learning experiments have explored a variety of signaling spaces such as sequences of letters (Kirby et al, 2008;, Carr et al, 2017Cornish et al, 2017), syllables , colors (Cornish et al, 2013), tones (Kempe et al, 2019) as well as drawn squiggles , tracings on a continuously moving pad (Galantucci, Kroos & Rhodes;, abstract graphical forms called Ferros (Cuskley, 2019), whistled pitch contours (Verhoef et al, 2014;, and manual gestures (Motamedi et al, 2019). These experiments have shown that both inter-generational transmission (Verhoef et al 2014) and referential communication (Little et al, 2017), can lead to the emergence of combinatorial structure.…”
Section: Combinatorial and Compositional Structurementioning
confidence: 99%
“…More generally, such non-arbitrary relationships involve a degree of homeomorphism between the topologies of the signal and meaning spaces (Little et al, 2017b), a relationship that has also been termed relative iconicity. For example, both in natural languages and in artificial signaling systems longer signals tend to be associated with bigger referents or more complex meanings (Lewis & Frank, 2016, Little et al, 2017Kempe et al, 2019). Furthermore, words with similar sounds tend to have similar meanings (Monaghan et al, 2014;Tamariz, 2008), and letters with similar shapes tend to map onto similar sounds (Jee, Tamariz & Shillcock, under review).…”
Section: Combinatorial and Compositional Structurementioning
confidence: 99%
See 1 more Smart Citation
“…However, children's innovative potential is more apparent in the acquisition of instrumental skills rather than social conventions . Because language is a social convention, and children are faithful imitators of social conventions, it is doubtful that children are the primary agents of linguistic innovation and language change …”
Section: Learning Complex Languages: the Role Of Playmentioning
confidence: 99%
“…97 Because language is a social convention, and children are faithful imitators of social conventions, 97 it is doubtful that children are the primary agents of linguistic innovation and language change. [98][99][100] Instead, we argue that a propensity for playful innovation that has been cemented with respect to tools and objects during childhood reaches into adolescence and adulthood, where it may provide one engine for linguistic innovation and change that has allowed language to accommodate the complex social conditions made possible by self-domestication. As argued earlier, to extend playing behavior into adulthood is one of the hallmarks of domestication.…”
Section: Imitation Ensures Transmission Of Cultural Traits Like Toolsmentioning
confidence: 99%